2001
DOI: 10.1002/1531-8249(200101)49:1<35::aid-ana8>3.0.co;2-j
|View full text |Cite
|
Sign up to set email alerts
|

Sexual arousal and orgasm in women: Effects of spinal cord injury

Abstract: Sexual disorders are common in women; however, the neurological basis of female sexual response has not been adequately investigated. This information is necessary to characterize the impact of various neurological disorders on sexual arousal in women and to develop appropriate management strategies for sexual dysfunction. To assess the spinal mediation of sexually stimulated genital vasocongestion in women, we conducted two laboratory‐based, controlled analyses: (1) of women's genital, subjective, and autonom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
132
0
10

Year Published

2004
2004
2018
2018

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 228 publications
(145 citation statements)
references
References 29 publications
3
132
0
10
Order By: Relevance
“…The majority of women who reached an orgasm claimed to do so less frequently, with greater difficulty, and they described it as less pleasurable than before the injury. Sipski 3,13,14 publishes similar percentages in several of her studies, and congruent to our findings, does not find any relationship with neurological levels nor the ASIA grade. In one of their studies, Spiski et al 14 found that women with SCI require more time and more intense stimulation to reach orgasm than the women in the control group, yet the subjective characteristics of the orgasm did not vary between the two groups nor with respect to their previous experiences.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…The majority of women who reached an orgasm claimed to do so less frequently, with greater difficulty, and they described it as less pleasurable than before the injury. Sipski 3,13,14 publishes similar percentages in several of her studies, and congruent to our findings, does not find any relationship with neurological levels nor the ASIA grade. In one of their studies, Spiski et al 14 found that women with SCI require more time and more intense stimulation to reach orgasm than the women in the control group, yet the subjective characteristics of the orgasm did not vary between the two groups nor with respect to their previous experiences.…”
Section: Discussionsupporting
confidence: 91%
“…Jackson and Wadley 11 in their report suggest that subjects with incomplete injury were more likely to report orgasm than those with complete injury. Sipski 3,13 does not find any relationship with neurological levels nor the ASIA grade, although in another study 14 reported that an intact sacral reflex arc is necessary for experiencing orgasm through direct genital stimulation.…”
Section: Introductionmentioning
confidence: 90%
“…14,16,17 The presence of genital sensation, indicative of sparing of the sacral reflex arc, significantly influences the likelihood of achieving orgasm. As mentioned previously, a more detailed analysis of orgasm in our study population will be presented and discussed in a forthcoming paper.…”
Section: Orgasm After Scimentioning
confidence: 99%
“…Later studies indicated that preservation of sensory input to the T11-L2 dermatomes was associated with the ability to experience psychogenic genital vasocongestion. 14,15 It is thought that approximately 50% of women with SCI have the ability to experience orgasm postinjury, 14,16,17 although there is a longer latency to reach orgasm. 14 One important component, however, appears to be sparing of the sacral reflex arc.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation